A low Lyman Continuum escape fraction of <10 per cent for extreme [O iii] emitters in an overdensity at z ∼ 3.5. Issue 1 (18th April 2018) - Naidu, Rohan P; Forrest, Ben; Oesch, Pascal A; Tran, Kim-Vy H; Holden, Bradford P
ABSTRACT: Recent work has suggested that extreme [O iii ] emitting star-forming galaxies are important to reionization. Relatedly, [O iii ]/[O ii ] has been put forward as an indirect estimator of the Lyman Continuum (LyC) escape fraction ( f esc ) at z ≳ 4.5 when the opaque IGM renders LyC photons unobservable. Using deep archival U -band (VLT/VIMOS) imaging of a recently confirmed overdensity at z ∼ 3.5, we calculate tight constraints on f esc for a sample ( N  = 73) dominated by extreme [O iii ] emitters. We find no LyC signal ($f_{\rm esc}^{\rm rel} < 6.3^{+0.7}_{-0.7} \hbox{ per cent}$ at 1σ) in a deep U -band stack of our sample (31.98 mag at 1σ). This constraint is in agreement with recent studies of star-forming galaxies spanning z  ∼ 1–4 that have found very low average f esc . Despite the galaxies in our study having an estimated average rest-frame EW([O iii ]λ5007) ∼ 400 Å and [O iii ]/[O ii ] ∼ 4 from composite SED fitting, we find no LyC detection, which brings into question the potential of [O iii ]/[O  ii ] as an effective probe of the LyC – a majority of LyC emitters have [O iii ]/[O ii ] > 3, but we establish here that [O iii ]/[O ii ] > 3 does not guarantee significant LyC leakage for a population. Since even extreme star-forming galaxies are unable to produce the $f_{\rm esc}\sim 10{-}15\hbox{ per cent}$ required by most theoretical calculations for star-forming galaxies to drive reionization, there must either be a rapid evolution of f esc between z ∼ 3.5 and the epoch of reionization, or hitherto observationally unstudied sources [e.g. ultrafaint low-mass galaxies with log ( M /M⊙ ) ∼ 7–8.5] must make an outsized contribution to reionization.